Clinical and laboratory assessment of the effectiveness of early rehabilitation of patients with stroke using assistive robotic tools - E. S. Koroleva; V. M. Alifirova; N. G. Brazovskaya; D. M. Plotnikov; L. A. Levchuk; A. S. Boyko; S. G. Zapekin; A. S. Semenenko; N. G. Kataeva; S. A. Ivanova (Бюллетень сибирской медицины)
Background. Using external robotic tools in rehabilitation of patients after stroke could activate neuroplasticity mechanisms, thus reducing the ischemic area and improving the neurological outcome of the disease.Aim. To evaluate the effectiveness of early rehabilitation of stroke patients in Tomsk Regional Stroke Center using assistive robotic tools by correlational analysis of clinical and laboratory biomarkers of brain neuroplasticity.Materials and methods. The study included 68 patients who suffered from stroke of the middle cerebral artery. Early rehabilitation was carried out in Tomsk Regional Stroke Center using assistive robotic tools according to the protocol. Neurotrophic factors in blood serum were measured by the enzyme-linked immunosorbent assay. The severity of neurological disorders was characterized based on the Fugl – Meyer assessment scale (FMA).Results. The clinical effectiveness of early motor rehabilitation in Tomsk Regional Stroke Center is confirmed by the statistically significant increase on the FMA scale by 5.2 ± 2.4 points (p = 0.008). Positive association between neurotrophic factors in blood serum and FMA total score enables to consider the resulting data as an evidence of neuroplasticity activation associated with the use of robotic electromechanical technologies.